Annual emissions and air-quality impacts of an urban area district-heating system: Boston case study - Bernow, S. S.; McAnulty, D. R.; Buchsbaum, S.; Levine, E. (Argonne National Laboratory, 1980)
A district-heating system, based on thermal energy from power plants retrofitted to operate in the cogeneration mode, is expected to improve local air quality. This possibility has been examined by comparing the emissions of five major atmospheric pollutants, i.e., particulates, sulfur oxides, carbon monoxide, hydrocarbons, and nitrogen oxides, from the existing heating and electric system in the City of Boston with those from a proposed district heating system. Detailed, spatial distribution of existing heating load and fuel mix is developed to specify emissions associated with existing heating systems. Actual electric-power-plant parameters and generation for the base year are specified. Additional plant fuel consumption and emissions resulting from cogeneration operation have been estimated. Six alternative fuel-emissions-control scenarios are considered. The average annual ground-level concentrations of sulfur oxides are calculated using a modified form of the EPA's Climatological Dispersion Model. This report describes the methodology, the results and their implications, and the areas for extended investigation. The initial results confirm expectations. Average sulfur oxides concentrations at various points within and near the city drop by up to 85% in the existing fuels scenarios and by 95% in scenarios in which different fuels and more-stringent emissions controls at the plants are used. These reductions are relative to concentrations caused by fuel combustion for heating and large commercial and industrial process uses within the city and Boston Edison Co. electric generation.